MOISTURE SORPTION IN ARTIFICIALLY AGED WOOD-PLASTIC COMPOSITES - B. Kristoffer Segerholm, (BioResources, 2012)
Moisture sorption in wood-plastic composites (WPCs) affects their durability and dimensional stability. In certain outdoor exposures, the moisture properties of WPCs are altered due to e.g. cracks induced by swelling and shrinkage of the components, as well as UV degradation or biological attack. The aim of this work was to study the effect of different artificial ageing routes on the moisture sorption properties of WPCs. Extruded WPCs were prepared with either unmodified or acetylated wood and recycled high-density polyethylene (HDPE). The WPC samples were artificially aged involving water soaking, artificial weathering, and white- or brown-rot decay in different combinations. After the ageing, the samples were conditioned in either 65% or 90% relative humidity (RH) until equilibrium moisture content was reached. A dynamic moisture sorption analyzer was used to monitor the sorption rate of samples subjected to a climate change from 65% to 90% RH. Scanning electron microscopy was used to study the surface morphology of the aged composites. Results showed that the artificial weathering caused cracking of the HDPE matrix at the composite surface, as well as a wood-matrix debonding, resulting in an increased moisture sorption rate. The WPC samples subjected to white-rot decay showed the highest moisture sorption rate.